(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
In this work, the effect of voltage and concentration on the properties of zinc powder (purity, morphology, and apparent density) that produced by electrodeposition process from industrial waste (galvanized steel) was studied. In Electrodeposition process, used sulfuric acid H₂SO₄ with concentration 0.2M and zinc sulphate heptahydrate ZnSO₄.7H₂O in three different concentrations (100, 75, and 50) M, The time of deposition is 10 mins, three electrodes were used, the distance between electrodes was 3cm for all experiments and the PH of solutions were 0.3, 0.4, 0.6 for three concentrations respectively. The voltages that used were (2, 3, 4, 6, 8, and11) V. First of all, the morphology of zinc powder for all experiments was dendritic. The effect of voltage on the apparent density in ranging was from 1.2 to 0.71 gm. /cm3 in 100M for voltages from 2V to 11V, it was from 0.94 to0.60 gm. /cm3 in 75M, and it was from 0.80 to 0.50 gm. /cm3 in 50M concentration. The purities increased with decrease of zinc ion concentration were (89.51, 92.78, and 95.48) for three different concentrations of same voltage 2V. The highest purity of Zn powder was 95.58 in 6V in 50M concentration.